Diagnostic Challenges in Late Onset Multiple Acyl-CoA Dehydrogenase Deficiency: Clinical, Morphological, and Genetic Aspects - Lupica, Antonino; Oteri, Rosaria; Volta, Sara; Ghezzi, Daniele; Drago, Selene Francesca Anna; Rodolico, Carmelo; Musumeci, Olimpia; Toscano, Antonio (Frontiers in Neurology, 2022)
Background Multiple Acyl-CoA Dehydrogenase Deficiency (MADD) is an autosomal recessive disorder of fatty acid oxidation due to deficiency of mitochondrial electron transfer chain. The late onset form is characterized by exercise intolerance, muscle weakness and lipids storage in myofibers. Most of MADD patients greatly benefit from riboflavin supplementation. Patients and Methods A retrospective study was conducted on patients with a diagnosis of vacuolar myopathy with lipid storage followed in our Neuromuscular Unit in the last 20 years. We selected 14 unrelated patients with diagnosis of MADD according to clinical morphological and biochemical aspects. Clinical features, blood tests including serum acylcarnitines, EMG and ENG were revised. Muscle biopsy was performed in all, one underwent also a sural nerve biopsy. Gene sequencing of ETFA, ETFB, ETFDH was performed as first tier genetic analysis followed by an hyperckemia NGS gene panel in patients with undefined genotype. Results At clinical evaluation at onset all our patients showed fatigue and muscle weakness; 4 patients showed difficulties in chewing, 4 patients complained of dysphagia, 2 patients had a dropped head, and a patient had an unexpected ataxia with numbness and dysesthesia. Laboratory blood tests revealed variable increase of serum CK (266 to 6500) and LDH levels (500 to 2000). Plasma acylcarnitines profile evidenced increased levels of different chains intermediates. EMG was either normal or showed myogenic or neurogenic patterns. ENG demonstrated a sensory neuropathy in two patients. Muscle biopsies showed a vacuolar myopathy with variable increase of lipid content. Nerve biopsy evidenced an axonal degeneration with loss of myelinated fibers. ETFDH genetic analysis identify pathogenic variants in 10 patients. Patients were treated with high doses of riboflavin (400 mg/die). All of them showed a rapid muscle strength improvement and laboratory tests normalization. Neuropathic symptoms did not improve. Conclusions Our data confirmed that clinical features in MADD patients are extremely variable in terms of disease onset and symptoms making diagnosis difficult. Laboratory investigations as serum acylcarnitines profile and muscle biopsy may strongly address the diagnosis. The favourable response to riboflavin supplementation strengthens the importance of an early diagnosis of these disorders among the spectrum of metabolic myopathies.